Determinants of Bank Profitability in US and the Impact of Subprime Crisis on US Banking Industry - Zhang, Xiaofen (2010)
This paper examines how bank-specific characteristic as well as macroeconomic conditions affect US banks’ profitability during the period 2002 to 2009. In order to develop out of previous work, this study also investigates the impact of subprime crisis on bank performance. The results indicate that efficient expense management, liquidity and diversified income source are the main determinants of bank profitability. After the subprime crisis, liquidity, diversified income source as well as asset quality became more important factors that affecting bank performance. Key words: Banks, Performance, Profitability, US, Subprime crisis